Gordon Stretton: a study in multiple identities - Daniels, Jeff; Rye, Howard (Popular Music History, 2010)
A Liverpudlian of mixed Jamaican and Irish ancestry, William Masters, born in 1887, provides a fascinating study of a member of the African diaspora seeking and finding an artistic identity. After membership of a Lancashire clog-dancing troupe, he adopted a stage name, Gordon Stretton, in tribute to an Edwardian music-hall artist, then learnt to be a jazz drummer under the tutelage of visiting African-American musician Billy Dorsey. Stretton’s varied career subsequently took him to France and Argentina. He exemplifies the manner in which members of the African diaspora of very varied backgrounds were sucked into currently prestigious North American idioms.